If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x)(x + -1)(x + 4) = 12 Reorder the terms: x(-1 + x)(x + 4) = 12 Reorder the terms: x(-1 + x)(4 + x) = 12 Multiply (-1 + x) * (4 + x) x(-1(4 + x) + x(4 + x)) = 12 x((4 * -1 + x * -1) + x(4 + x)) = 12 x((-4 + -1x) + x(4 + x)) = 12 x(-4 + -1x + (4 * x + x * x)) = 12 x(-4 + -1x + (4x + x2)) = 12 Combine like terms: -1x + 4x = 3x x(-4 + 3x + x2) = 12 (-4 * x + 3x * x + x2 * x) = 12 (-4x + 3x2 + x3) = 12 Solving -4x + 3x2 + x3 = 12 Solving for variable 'x'. Reorder the terms: -12 + -4x + 3x2 + x3 = 12 + -12 Combine like terms: 12 + -12 = 0 -12 + -4x + 3x2 + x3 = 0 The solution to this equation could not be determined.
| 2(8*3x)-7+5x=-(7x*2) | | -2k^2-162=0 | | -26=2y-8(x-y) | | 6b=13b-221 | | 2(8+3x)-7+5x=-(7x-2) | | 11x+12y=13 | | 4(3x+5)=2(9x+16) | | 9x+7=8x | | -2(x+4)+5=6(x+2)+2 | | 5(3x-2y)-(x+6y)= | | -7n^2-488=0 | | X^2+19=33 | | 3(2-a)-4(-6-2a)= | | 4x-5=30 | | 100=4.625 | | 7x^2=0 | | -5x^2-500=0 | | 5(X+2)-2(2X+3)=34-5X | | -174-7z=-13z | | X^3-2x^2-4x+8=0 | | -3(5-9v)=25+7f | | 8(4x+7)=12k-4 | | 2x+5=X-8whatisx | | cosx-sinx=0 | | 8x^3+168x^2-176x=0 | | 7x^2y+4xy^2-6xy+yx= | | 333-5y=8 | | -4x=111-7x | | -0.67t-3=-5 | | 4y+10-5y-4= | | 33-5=8 | | 3x+7=6x-12 |